Analisis Kemampuan Pemahaman Konsep Siswa dalam Menyelesaikan Masalah Perbandingan Berdasarkan Teori Pirie-Kieren - Rochma, Nisha Ardianty; Suwanti, Vivi; Pranyata, Yuniar Ika Putri (JMPM: Jurnal Matematika dan Pendidikan Matematika, 2023)
The aim of the study was to describe the level of development students' conceptual understanding abilities based on the Pirie-Kieren theory using a qualitative approach and descriptive research. The results of the study show that students with low conceptual understanding abilities only meet 2 indicators of conceptual understanding ability, so these students are still at the Image having layer. Students with moderate conceptual understanding are able to fulfill 5 of the 7 indicators conceptual understanding ability, so these students are still in the observing layer. While students with high conceptual understanding abilities have fulfilled all indicators of conceptual understanding ability, only one student is still in the Sturcturing layer and one other student is already in the outermost layer (Inventising).